Entrepreneurship and Economic Transition - Ruta Aidis (Tinbergen Institute, 2003)
Identification of the entrepreneur's economic function has engaged economistsfor more than 200 years. In this paper we address the issue of entrepreneurship intwo distinct ways: a) as it has historically developed within the field of economicsand b) as it develops in the transitional context. In contrast to advanced westerneconomies, productive entrepreneurship cannot be taken for granted in transitioncountries. Therefore we propose a working definition and model for productiveentrepreneurship for transition countries. By means of a literature survey, wefurther present the main characteristics of entrepreneurship in Central EasternEuropean and Former Soviet Union countries. Entrepreneurship in Lithuaniaseems to not fit neatly into these two categories and its specific situation ishighlighted.
Keywords: M13; P2; P5; 330; Entrepreneurship; economics; transition economies; Entrepreneurship-Ansatz; Dogmengeschichte; Übergangswirtschaft; Osteuropa